Impact of chemical management on occupational health and safety in chemistry laboratories at a public university - Mendoza Rodas, Zoila Luz (2025)
This study investigated the influence of chemical management on occupational health and safety in chemistry laboratories at a public university. A basic methodology with a non-experimental design was employed, using a questionnaire applied to a sample of 30 teachers and technicians. The results revealed that 63.4% of the participants perceive a regular level of occupational health and safety, while 23.3% consider it inadequate and only 13.3% evaluate it as high. The analysis demonstrates a clear interdependence between chemical handling and occupational safety in these environments. The findings underline the need to implement a comprehensive approach that includes training, clear protocols and adequate resources to ensure a safe working environment. This study provides valuable information for future research and for the continuous improvement of safety practices in academic laboratories, with the aim of promoting a work environment that complies with current regulations and protects the health of workers.